Integral Health in Messina Strait: marine ecosystems, historical collections and human well-being - Giaccone, Thalassia; Mannino, Anna Maria; Ragazzola, Federica (O Mundo da Saúde, 2026)
The benthic ecosystems of the Strait of Messina, Laminaria ochroleuca Bachelot Pylaie 1824 forests and rhodolith beds, play a crucial role in promoting environmental and human health, offering essential Nature’s Contributions to People (NCP), such as climate regulation, food provision, and psychosocial benefits. Complementing these natural systems, the historical Herbarium “A. Pistone” documents the algal seascapes of the late 19th century and offers cultural, aesthetic, and educational values that enhance psychosocial well-being and strengthen emotional memory within local communities. Sustainable practices, such as scuba diving activities, citizen science initiatives, and awareness campaigns, are proposed as “People’s Contributions to Nature” (PCN), expressed through gratitude, empathy, affection, reciprocity, and spirituality. These actions promote mental and physical health by reducing stress, fostering social cohesion, and encouraging active lifestyles, while also supporting nature-based strategies for disease prevention through biodiversity conservation and improved ecosystem integrity. Future research will focus on taxonomic identification of herbarium specimens (using DNA barcoding and morphological analysis), biogeographical and biocoenotic studies, and quantitative assessments of ecosystem services. These analyses are essential to understand how these ecosystems mitigate climate change, reduce environmental health risks, and inform public health policies aimed at integrating ecosystem services into preventive strategies. To strengthen the human–nature relationship and promote integral health, participatory approaches, such as educational workshops, immersive experiences, and collaboration among fishing and mussel-farming communities, local authorities, and schools, are key components of integrated conservation and health promotion frameworks.